Home » Blog » Derive some properties of the product of ex with a polynomial

Derive some properties of the product of ex with a polynomial

Let

    \[ f(x) = e^x p(x) \qquad \text{where} \qquad p(x) = c_0 + c_1 x + c_2x^2. \]

  1. Prove that

        \[ f^{(n)} (0) = c_0 + nc_1 + n(n-1)c_2 \]

    where f^{(n)} denotes the nth derivative of f.

  2. Do part (a) in the case that p(x) is a cubic polynomial.
  3. Find a similar formula and prove it in the case that p(x) is a polynomial of degree m.

For all of these we recall from a previous exercise (Section 5.11, Exercise #4) that by Leibniz’s formula if h(x) = f(x)g(x) then the nth derivative h^{(n)}(x) is given by

    \[ h^{(n)} (x) = \sum_{k=0}^n \binom{n}{k} f^{(k)} (x) g^{(n-k)}(x). \]

So, in the case at hand we have f(x) = e^x p(x) and so

    \[ f^{(n)} (x) = \sum_{k=0}^n \binom{n}{k} p^{(k)}(x) e^x. \]

(Since the (n-k)th derivative of e^x is still e^x for all n and k.)

  1. Proof. From the formula above we have

        \[ f^{(n)}(0) = \sum_{k=0}^n \binom{n}{k} p^{(k)}(0) e^0 = \sum_{k=0}^n \binom{n}{k} p^{(k)}(0). \]

    But, since p(x) is a quadratic polynomial we have

        \begin{align*}  p(x) &= c_0 + c_1 x + c_2 x^2 \\[9pt]  p'(x) &= c_1 + 2c_2 x \\[9pt]  p''(x) &= 2c_2 \\[9pt]  p^{(k)} (x) &= 0 & \text{for all } k \geq 3. \end{align*}

    Hence, we have

        \begin{align*}   f^{(n)}(0) &= \binom{n}{0} p(0) + \binom{n}{1} p'(0) + \binom{n}{2} p''(0) \\[9pt]  &= c_0 + n c_1 + \frac{n(n-1)}{2} 2c_2 \\[9pt]  &= c_0 + n c_1 + n(n-1) c_2. \qquad \blacksquare \end{align*}

  2. If p(x) is a cubic polynomial we may write,

        \[ p(x) = c_0 + c_1 x + c_2 x^2 + c_3 x^3. \]

    Claim: If f(x) = e^x p(x) then

        \[ f^{(n)}(0) = c_0 + nc_1 + n(n-1)c_2 + n(n-1)(n-2)c_3. \]

    Proof. We follow the exact same procedure as part (a) except now we have the derivatives of p(x) given by

        \begin{align*}  p(x) &= c_0 + c_1 x + c_2x^2 + c_3x^3 \\[9pt]  p'(x) &= c_1 + 2c_2 x + 3c_3 x^2 \\[9pt]  p''(x) &= 2c_2 + 6c_3 x \\[9pt]  p^{(3)}(x) &= 6c_3 \\[9pt]  p^{(k)}(x) &= 0 & \text{for all } k \geq 4.  \end{align*}

    Therefore, we now have

        \begin{align*}  f^{(n)}(0) &= \sum_{k=0}^n \binom{n}{k} p^{(k)}(0) e^0 \\[9pt]  &= \sum_{k=0}^n \binom{n}{k} p^{(k)}(0) \\[9pt]  &= \binom{n}{0} p(0) + \binom{n}{1} p'(0) + \binom{n}{2} p''(0) + \binom{n}{3} p'''(0) \\[9pt]  &= c_0 + nc_1 + \frac{n(n-1)}{2} 2c_2 + \frac{n(n-1)(n-2)}{6} 6c_3 \\[9pt]  &= c_0 + nc_1 + n(n-1)c_2 + n(n-1)(n-2)c_3. \qquad \blacksquare \end{align*}

  3. Claim: Let p(x) be a polynomial of degree m,

        \[ p(x) = \sum_{k=0}^m c_k x^k. \]

    Let f(x) = e^x p(x). Then,

        \[ f^{(n)}(0) = \sum_{k=0}^m k! \binom{n}{k} c_k. \]

    Proof. Using Leibniz’s formula again, we have

        \[ f^{(n)}(0) = \sum_{k=0}^m \binom{n}{k} p^{(k)}(0). \]

    But for the degree m polynomial p(x), we know p^{(k)}(0) = k!c_k if 0 \leq k \leq m and p^{(k)} (0) = 0 for all k > m. Hence, we have

        \[ f^{(n)}(0) = \sum_{k=0}^m k! \binom{n}{k} c_k. \qquad \blacksquare \]

Point out an error, ask a question, offer an alternative solution (to use Latex type [latexpage] at the top of your comment):